MUSIGA Headquarters, Accra - Blagogee, J. S. K. (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of Postgraduate Diploma in Architecture,